2020
DOI: 10.21203/rs.3.rs-35112/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA LINC00342 contributes to the growth and metastasis of colorectal cancer via targeting miR-19a-3p/NPEPL1

Abstract: Background Long intergenic non-protein coding RNA 342 (LINC00342) has been identified as a novel oncogene, however, the functional role of LINC00342 in colorectal cancer (CRC) remained unclear. Methods The expression of LINC00342 was detected by real-time PCR. Cell proliferation, migration and invasion and xenograft model were examined to analyze the biological functions of LINC00342 in vitro and in vivo. Dual-luciferase reporter and RNA immunoprecipitation (RIP) assays were used to identify the target interac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…was involved in the ceRNA regulatory network and functioned as an endogenous miRNA sponge to bind to miR-19a-3p and regulated its function. In line with our nding, Chen et al reports that ectopic LINC00342 expression facilitates NSCLC cell proliferation, migration, and invasion by sponging miR-203a-3p [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…was involved in the ceRNA regulatory network and functioned as an endogenous miRNA sponge to bind to miR-19a-3p and regulated its function. In line with our nding, Chen et al reports that ectopic LINC00342 expression facilitates NSCLC cell proliferation, migration, and invasion by sponging miR-203a-3p [27].…”
Section: Discussionsupporting
confidence: 91%
“…High expression of LINC00342 predicts a poor prognosis in NSCLC [26]. Knockdown of LINC00342 inhibits NSCLC cell proliferation, migration and invasion [27]. However, the expression and function of LINC00342 were unknown in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-203a-3p inhibited cell proliferation, migration and invasion in lung adenocarcinoma by FBXL19-AS1/miR-203a-3p axis [31]. MiR-203a-3p served as a target of LINC00342 to inhibit cell proliferation, colony formation, migration and invasion in non-small cell lung cancer [32]. Recently, bioinformatics analysis indicated that the expression of miR-203a-3p was dramatically decreased in the bronchial epithelial cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although asthma is commonly diagnosed in childhood, it occurs in all age groups [3]. Ra et al reported that there was no significant difference between the prevalence rate of the elderly (>65) and that of the young people (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) [4]. A lot of stimuli, including cold air and exercise, and other risk factors such as smoking, obesity and rhinitis contribute to asthma incidence [5][6][7].…”
Section: Introductionmentioning
confidence: 99%